Epibenthic faunal assemblages in the mudflats of Northern Negros - Deldo, Ressa V (Miagao, Iloilo University of the Philippines Visayas, 2019)
Pushnets are among the commonly used gears in the intertidal mudflats in Northern Negros. This study was conducted to characterize the epibenthic faunal assemblages in the mudflat area off the coast of Cadiz City in Northern Negros using pushnets. Two (2) data sets were collected : 1) daily catch and effort records from local pushnetters used to determine patterns in fishery catches ; and 2) samples consisting of the entire catch in two (2) locations (stations) used to characterize species abundance and composition. Sampling was done weekly from December 2011 to December 2012 on two (2) stations done at night (dusk to dawn) and during low tides.. The intertidal mudflats in northern Negros has a substantial number of epibenthic faunal assemblages and is dominated by four (4) major species groups with crabs-Portunus pelagicus having the highest abundance and biomass. There is seasonality in the area with the SW having higher mean catch rates than the NE monsoon months. There is also spatial difference (between stations) particularly during SW monsoon months wherein mean catch rates in Stn 2 is higher than Stn 1. Almost all the species caught are small, sessile and slow moving organisms. Most of these are juveniles and not yet sexually mature highlighting the importance of these intertidal mudflats as nursery and feeding ground. Pushnets, if still continuous to be unregulated may exhaust the coastal fishery resources of the area with some of the major species being heavily exploited. This can eventually affect the overall productivity of these habitat and in turn affect the overall productivity of Visayan Sea.
Thesis (M.S. Biology) -- Miagao, Iloilo : University of the Philippines Visayas, 2019.